Routine hematology and blood sugar profile in premature infants with low birth weight at Dustira hospital in 2021 - Triningtyas, Anastasia Yani; Ayukarningsih, Yoke; Ramdan, Deanita Savira (Sean Institute, 2024)
Premature babies are babies born at a gestational age of less than 37 weeks. Low birth weight babies (LBW) are babies born with a body weight of less than 2500 grams. Premature babies face various risks of morbidity and death after birth. Various health problems that arise occur because premature babies are born with organs that have not been fully formed, causing problems or disorders of the body's system. One of the problems that often occurs in premature infants is disorders of the hematological system. Some of the hematological disorders that often occur in premature infants include hemolysis, anemia, polycythemia and thrombocytopenia. . In addition, premature babies also have a limited supply and source of carbohydrate production for metabolism because the organs involved in metabolic processes such as the liver, pancreas, brain and endocrine glands are not yet fully formed. Therefore, premature babies are prone to experiencing hyperglycemia or hypoglycemia. This research is a type of quantitative descriptive research using secondary data originating from medical records to determine hematological examinations in premature infants with LBW babies at Dustira Hospital in 2021 which consists of examination of hemoglobin, hematocrit, erythrocytes, leukocytes, platelets, erythrocyte index values and blood sugar. when. Sampling used the total sampling method with a sample size in this study taken based on data on premature babies with low birth weight at Dustira Hospital in 2021, totaling 38 babies. An overview of hemoglobin, platelet levels, erythrocyte index values and blood sugar during the study subjects most of these have normal values while others have decreased values of erythrocytes, leukocytes, hematocrit. Further research was carried out to identify the etiology and risk factors for premature birth defects with LBW starting from intrauterine as well as extraluterine and differentiate between sick premature babies and healthy premature babies.